Gambling advocacy: lessons from tobacco, alcohol and junk food - Samantha L. Thomas; Jennifer David; Melanie Randle; Mike Daube; Kate Senior (Elsevier, 2016)
Abstract Objective: To explore the attitudes and opinions of public health experts in gambling and related unhealthy commodity industries towards the tactics used by the gambling industry to prevent reform and the advocacy responses to these tactics. Methods: In‐depth interviews (30-60 minutes) with a convenience sample of 15 public health experts and stakeholders with a public health approach to gambling (n=10), or other unhealthy commodity industries (food, alcohol, tobacco, n=5). Results: Participants described the influences of political lobbying and donations on public policy, and industry framing of problem gambling as an issue of personal responsibility. Industry funding of, and influence over, academic research was considered to be one of the most effective industry tactics to resist reform. Participants felt there was a need to build stronger coalitions and collaborations between independent academics, and to improve the utilisation of media to more effectively shift perceptions of gambling harm away from the individual and towards the product. Conclusions and implications: Gambling industry tactics are similar to the tactics of other unhealthy commodity industries. However, advocacy initiatives to counter these tactics in gambling are less developed than in other areas. The formation of national public health coalitions, as well as a strong evidence base regarding industry tactics, will help to strengthen advocacy initiatives.